Is Bigger Better? Corpus and Dictionary Use in the Search for Compounds, Collocations, Derived Forms and Fixed Expressions - Royle, Phaedra; Richardson, Isabelle; Boisvert, Sophie; Bourguignon, Nicolas (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractIn the course of the development of a bilingual dictionary, a number of monolingual source language and target language dictionaries, bilingual dictionaries, and text corpora are typically used as tools to create entries. When dealing with words that occur at a high frequency in the corpus, determining which collocations, compounds, derived forms and fixed expressions are to be included in the dictionary is an additional complication. This paper presents the relative merits of using dictionary and corpus sources for searching for this type of information. We present frequency searching as an efficient and useful tool for corpus analysis, especially in the case of high-frequency words.